2021
DOI: 10.3390/nano11051202
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Generation and Detection of Coherent Ag Phonons in Black Phosphorus

Abstract: Black phosphorus (BP) has attracted great attention due to its layer-tuned direct bandgap, in-plane anisotropic properties, and novel optoelectronic applications. In this work, the anisotropic characteristics of BP crystal in terms of the Raman tensor and birefringence are studied by investigating polarization dependence in both the generation and detection of Ag mode coherent phonons. While the generated coherent phonons exhibit the typical linear dichroism of BP crystal, the detection process is found here t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We mechanically exfoliated BP flakes using sticky tape from a bulk crystal and transferred them onto transparent fused silica (FS) substrates [23,24]. Optical images of two such flakes are shown in figures 1(a) and (b), where the relatively flat regions denoted by S1 to S4 were selected for further optical investigations.…”
Section: Sample Preparationmentioning
confidence: 99%
“…We mechanically exfoliated BP flakes using sticky tape from a bulk crystal and transferred them onto transparent fused silica (FS) substrates [23,24]. Optical images of two such flakes are shown in figures 1(a) and (b), where the relatively flat regions denoted by S1 to S4 were selected for further optical investigations.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The zoomed-in plot of ΔT/T in the inset of Fig. 2b exhibits a transmission change originated from the lattice vibrations in the BP layer [29][30][31][32] . When the exponential and slowly varying components are removed from the pump-probe signal (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…[205][206][207][208] The different modes and the frequencies at which a system vibrates depend on its shape, composition, and surrounding medium. 205,[209][210][211][212][213] Generation and characterization of phonons and measurement of the different oscillation mode frequencies is usually done by employing pump-probe techniques. The study of the different mechanical oscillation modes is of fundamental importance as it provides information regarding mode lifetimes (and indirectly the losses within a certain material, the nature of forces between layers in van der Waals materials, and the nature of the adhesion of nanostructures to a substrate, to name a few examples.…”
Section: Pump-probementioning
confidence: 99%
“…212,215,236,242,243 For example, Arregui et al studied the generation of coherent acoustic phonons with frequencies on the order of 100's GHz in topological nanocavities, 237 Lin K. et al demonstrated the generation of acoustic pulses injecting light carriers in piezoelectric materials, 238 and Lee et al and Miao et al studied the generation and detection of coherent acoustic phonons in black phosphorus. 209,239 The generation and propagation of coherent longitudinal acoustic phonons along the cross-plane direction have also been studied in twodimensional systems, such as organic-inorganic hybrid perovskites, 244 van der Waals InSe layered material, and InSe/hBN heterostructures, 245 using picosecond ultrasonic pump-probe techniques. Time-domain pump-probe experiments have also enabled the exploration of ultrafast far-from-equilibrium phonon behavior in van der Waals thin films.…”
Section: Pump-probementioning
confidence: 99%
See 1 more Smart Citation